Dysregulation of miR-577, miR-505-3p, miR-3682-3p, and miR-4661 in Breast Cancer Patients Based on Estrogen Receptor Status: - Moradi, Arman; Rahmani, Saeid; Jafarbeik Iravani, Narges; Esmaeili, Rezvan; Mowla, Seyed Javad; Majidzadeh-A, Keivan (Galen Medical Journal, 2022)
Background: Breast cancer is one of the most common malignancies and the second leading cause of cancer-related death in women. Approximately 75% of all breast cancers are estrogen receptor-positive (ER+ ) and highly responsive to endocrine therapy. MicroRNAs (miRNAs) are short non-coding RNA with a pivotal role in mammal cells by regulating gene expression. Hence, this study aimed to evaluate the miRNAs expression in various breast cancer subtypes. Materials and Methods: In this study, after total RNA extraction and cDNA synthesis, expressions of miR-577, miR-505-3p, miR-3682-3p, and miR-4661-5p were investigated in 36 breast cancer samples of ER+ and ER- types and compared with 18 normal adjacent tissues by real-time polymerase chain reaction. Also, diagnostic values of miRNAs were determined based on receiver operating characteristic (ROC) by calculating the area under the curve (AUC). Results: Downregulation of miR-577 and miR-505-3p were detected in breast cancer samples, significantly in the ER+ subtype compared to ER- subtype (P<0.001). Also, we showed upregulation of miR-3682-3p and miR-4661-5p in breast cancer tissues compared to normal tissues. Compared to the ER+ subtype, the miR-3682-3p expression significantly decreased in the ER- subtype (P<0.001). However, there was no significant difference between ER+ and ER- subtypes in the term of miR-4661-5p (PËƒ0.05). The ROC analysis demonstrated that miR-577 and miR-505-3p have acceptable diagnostic values, and miR-3682-3p has a relatively proper diagnostic value in diagnosing breast cancer. Conclusion: Our results revealed that miR-577 and miR-505- 3p could be used as biomarkers for the diagnosis of breast cancer, especially in ER+ subtype.